Influence of the coupled support to the profitability of the vegetable crops sector - Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The purpose of this paper is to analyze the current state of vegetable sector and especially soybeans, rice, beets, hemp, hops receiving support coupled with subsidy on the surface as direct pay. The analysis takes into account a number of relevant indicators for both the performance of the sector in order to stimulate farmers for investments in certain crops and for farmers' incomes, meaning that coupled support may influence the profitability of crops to the detriment of crops declared as the profitable agricultural plant. In principle, each culture deals with analytical situation every technical and economic indicator focusing on highlighting gaps profitability. Examine where each culture in terms of the indicators considered in the study and make some concluding remarks about the current state of economic development of the vegetable sector and studied plants and the need to grant coupled support to maintain surfaces that are cultivated in present.
Keywords: O12; P50; Q18; Q57; 330; support coupled; vegetable sector; technical and economic indicators; profitability